2019
DOI: 10.1097/iae.0000000000002720
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Vitreoretinal Surgery Improves Surgical Accuracy Compared With Manual Surgery

Abstract: Robot-assisted vitreoretinal surgery increases precision and limits tissue damage compared with manual surgery especially for the novice surgeon. The Eyesi Simulator is a feasible platform for investigating robot-assisted vitreoretinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…They could also be used to carry out many of the tasks deemed thankless, dirty or dangerous during the pandemic, such as decontamination, waste delivery and handling, or monitoring quarantine compliance [ 71 , 72 ]. Within this context, the majority of studies into the effects of RAS are based on analyses of healthcare professionals’ assessments, which generally indicate positive effects on surgical intervention risk reduction, efficiency, and quality, and on the minimisation and subsequent recovery of costs linked to such interventions [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They could also be used to carry out many of the tasks deemed thankless, dirty or dangerous during the pandemic, such as decontamination, waste delivery and handling, or monitoring quarantine compliance [ 71 , 72 ]. Within this context, the majority of studies into the effects of RAS are based on analyses of healthcare professionals’ assessments, which generally indicate positive effects on surgical intervention risk reduction, efficiency, and quality, and on the minimisation and subsequent recovery of costs linked to such interventions [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, because of their ability to be programmed and their exact precision through stereoscopic vision in an area of interest, scalable movements, a wider range of axial movement [ 41 ] and the degree of computational accuracy [ 42 ], robots enable the specialist to better access risky areas or areas where there is no room for error. By doing so, RAS improves functional outcomes [ 26 , 27 , 28 , 29 , 30 ] and reduces morbidity rates for certain procedures [ 31 , 43 ]. Furthermore, RAS reduces the risk of surgery-related adverse events [ 43 , 44 , 45 ] by reducing operating times and technical errors, by improving access to areas of the body that are hard to reach, and by improving outcomes by eliminating (or minimising) the potential for human error, such as a surgeon’s tremors and vulnerability to fatigue [ 25 ], thereby helping the patient to recover faster and ensuring that the patient’s hospital stay is shorter [ 46 , 47 , 48 ].…”
Section: Hypotheses and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical standardization provides several benefitsrapid assessment of procedures and their validity, elimination of complications, rapid introduction and dissemination, and most important a limited learning curve for surgeons at all levels of experience. Simulators have shown both in ophthalmology and beyond, that robotics levels the playing field between experienced and novice surgeons [7,8]. Gene therapy, a highly priced, immunogenic product, which requires delivery to the subretinal space without reflux or breech of Bruch's membrane, using a slow infusion over several minutes can be done safely, and reproducibly using robotics.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…In a recent randomized trial, the Preceyes Surgical System has been shown to have a significant beneficial effect on surgical accuracy and tissue treatment in vitreoretinal procedures, when compared to manual surgery (Forslund Jacobsen et al. 2019). The effects on tissue treatment were only significant for novice vitreoretinal surgeons, and the study further concluded that robot‐assisted vitreoretinal surgery was significantly slower than manual surgery (Forslund Jacobsen et al.…”
Section: Introductionmentioning
confidence: 99%